ITRAQ-Based Quantitative Proteomics Reveals the Proteome Profiles of Primary Duck Embryo Fibroblast Cells Infected with Duck Tembusu Virus. (27th January 2019) - Hu, Feng; Li, Yufeng; Yu, Kexiang; Huang, Bing; Ma, Xiuli; Liu, Cunxia; Guo, Xiaozhen; Song, Minxun; Wu, Jiaqiang
Abstract : Outbreaks of duck Tembusu virus (DTMUV) have caused substantial economic losses in the major duck-producing regions of China since 2010. To improve our understanding of the host cellular responses to virus infection and the pathogenesis of DTMUV infection, we applied isobaric tags for relative and absolute quantification (iTRAQ) labeling coupled with multidimensional liquid chromatography-tandem mass spectrometry to detect the protein changes in duck embryo fibroblast cells (DEFs) infected and mock-infected with DTMUV. In total, 434 cellular proteins were differentially expressed, among which 116, 76, and 339 proteins were differentially expressed in the DTMUV-infected DEFs at 12, 24, and 42 hours postinfection, respectively. The Gene Ontology analysis indicated that the biological processes of the differentially expressed proteins were primarily related to cellular processes, metabolic processes, biological regulation, response to stimulus, and cellular organismal processes and that the molecular functions in which the differentially expressed proteins were mainly involved were binding and catalytic activity. Some selected proteins that were found to be differentially expressed in DTMUV-infected DEFs were further confirmed by real-time PCR. The results of this study provide valuable insight into DTMUV-host interactions. This could lead to a better understanding of DTMUV infection mechanisms.